TREATMENT RELATED MORTALITY IN ADOLESCENTS AND YOUNG ADULTS WITH ACUTE LYMPHOBLASTIC LEUKEMIA - Muhammad Umer Saleem; Abdukadirova Nargiza Batirbekovna (World Scientific Research Journal, 2025)
Introduction: Acute lymphoblastic leukemia is a malignant disease classified on the basis of B cell versus T cell lineage. More than two thirds of cases of ALL are B cell phenotype. B cell ALL is primarily a disease of children less than 6 years old and second peak in adults more than 60 years. T cell ALL presents in late childhood and adolescents. Both B and T cell ALL occur more frequently in males than females. The cause of ALL is unknown but it may be associated with ionizing radiation and unidentified infectious agents.